Ultra-High-Performance Liquid Chromatography–Tandem Mass Spectrometry Analysis of Δ9-Tetrahydrocannabinol and Cannabidiol in Commercial Suk-Saiyasna Herbal Remedy: Applying Hansen Solubility Parameters for Sample Extraction to Ensure Regulatory Compliance - Suwimon Sumontri; Wanna Eiamart; Sarin Tadtong; Weerasak Samee (Pharmaceuticals)
Background: Suk-Saiyasna is a traditional Thai herbal remedy that comprises 12 distinct herbs. Among these, cannabis leaves constitute 12 of the total 78 components in this formulation. This study specifically examines the portion of the cannabis plant, which accounts for approximately 15.8% of the overall herbal composition used in the entire remedy. According to the Thailand Narcotics Act of 2022, the Δ9-tetrahydrocannabinol (Δ9-THC) concentration in herbal extracts must not exceed 0.2% by weight. This study aims to quantify the levels of Δ9-THC and cannabidiol (CBD) in commercial Suk-Saiyasna products. Methodology: This research utilizes Hansen Solubility Parameters (HSPs) to identify the optimal solvent for ultrasonic extraction, thereby maximizing cannabinoid yield. An advanced method was developed employing ultra-high-performance liquid chromatography–tandem mass spectrometry (UHPLC-MS/MS), compliant with AOAC standards to meet regulatory guidelines. The method validation emphasized specificity, linearity, sensitivity, accuracy, and precision. Results: Dichloromethane was chosen due to its favorable HSP values, enabling highly efficient extraction of Δ9-THC and CBD, achieving recovery rates of over 99.9% after the second extraction. This investigation benefits from the accuracy of the UHPLC-MS/MS technique in quantifying cannabinoids in commercial products, with Δ9-THC concentrations observed between 0.00231% and 0.14218%, and CBD concentrations ranging from 0.00002% to 0.01541%, all remaining below the legal limit. Conclusions: The variability in cannabinoid concentrations among various commercial products highlights the need for standardization in the herbal industry. This finding underscores the critical role of rigorous quality control measures in ensuring the safety and efficacy of cannabis-derived products.